ChemInform Abstract: Cu—Pd/γ‐Al2O3 Catalyzed the Coupling of Multi‐Step Reactions: Direct Synthesis of Benzimidazole Derivatives. Issue 50 (November 2016) - Feng, Feng; Ye, Jia; Cheng, Zheng; Xu, Xiaoliang; Zhang, Qunfeng; Ma, Lei; Lu, Chunshan; Li, Xiaonian
Abstract: Transfer hydrogenation and subsequent cyclization of o‐nitroaniline with alcohols, catalyzed by the title multifunctional catalyst, affords benzimidazole derivatives in high yields.